Determinan faktor peningkatan kualitas hidup manusia dan ketimpangan pendapatan di ASEAN-8 periode 2010-2023 - Nuraini Chaniago; Raden Ajeng Entaresmen; Azizah Amelia Eka Susanti (LPMP Imperium, 2025)
This study aims to analyze economic factors influencing the Human Development Index (HDI) and Gini Ratio in eight ASEAN countries during 2010–2023. Using secondary data and panel data regression analysis, the findings indicate that per capita income, inflation, and labor force significantly affect HDI. Additionally, a negative relationship between HDI and Gini Ratio was identified, implying that improved human development can reduce income inequality. However, the results also highlight that economic growth does not always enhance life quality due to unequal distribution. Inclusive and redistributive policies in education, healthcare, and employment are essential to enhance HDI and reduce income disparities across the region.